Adobe photoshop 5 advanced digital images (Against the Clock series., 1999)
The AGAINST THE CLOCK library consists of nineteen highly consistent and effective modules, engineered specifically to meet the needs of commercial, educational, and individual desktop publishing users, instructing them in the use of the software that impacts their industry.